NEW OXALATO AND BENZOATO ADDUCTS CONTAINING A SnR3 or SnR2 RESIDUE (R=Me, Bu, Ph): SYNTHESIS, INFRARED AND MOSSBAUER STUDIES - YAYA SOW; LIBASSE DIOP (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
On allowing (i-Bu2NH2)2C2O4, (Cy2NH2)2C2O4.2H2O, (Pr2NH2)2C2O4, Pr2NH2HC2O4, (Me4N)2C2O4.2H2O or Cy2NH2O2CPh to react with SnPh3Cl, SnBu3Cl or SnMe3Cl, the seven studied adducts were obtained and studied by infrared and Mössbauer techniques. The suggested structures are discrete, the oxalate behaving as a non coordinating entity, only involved in hydrogen bonding while the benzoate is a mono-, bichelating or a monocoordinating ligand, the environments around the tin centres being trans or cis trigonal bipyramidal. When extra hydrogen bonds are considered involving free OH groups, a supramolecular architecture may be obtained. The key role of both the cation and the water molecules in the structures is noteworthy.